Determinan Keuangan Keperilakuan Heuristic dan Herding Analysis terhadap Keputusan Investasi Berbasis Syariah - Rozak, Abdul; Nugraha, Nugraha; Sari, Maya (Management Study Program, Faculty of Economic, Universitas Samudra, Indonesia, 2023)
Increasing investor interest in investing will certainly increase transaction activity in capital market, so that it will have an impact on the smooth running of company's operations. Business activities that run well and safely will increase the rate of economic growth. Relatively affordable investment capital as launched by Indonesia Stock Exchange since 2015 by holding the